2004
DOI: 10.1111/j.1365-313x.2004.02177.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of AtCHX17, a member of the cation/H+ exchangers, CHX family, from Arabidopsis thaliana suggests a role in K+ homeostasis

Abstract: SummaryThe Arabidopsis genome contains many sequences annotated as encoding H + -coupled cotransporters. Among those are the members of the cation:proton antiporter-2 (CPA2) family (or CHX family), predicted to encode NaAtCHX17, a member of the CPA2 family, was selected for expression studies, and phenotypic analysis of knockout mutants was performed. AtCHX17 expression was only detected in roots. The gene was strongly induced by salt stress, potassium starvation, abscisic acid (ABA) and external acidic pH. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
113
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(115 citation statements)
references
References 55 publications
2
113
0
Order By: Relevance
“…Our results and model are consistent with genetic studies of a related protein, CHX17. K 1 starvation induced an increase of CHX17 transcripts in wild-type plants; and K 1 starvation caused a 20% decrease in K 1 content of chx17 mutant roots (Cellier et al, 2004). To offset alkalization of the cytosol in yeast grown at pH 7.5, we suggest that antiporters, like CHX20, neutralize cytosolic pH by mediating K 1 exchange for H 1 release from acidified compartments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results and model are consistent with genetic studies of a related protein, CHX17. K 1 starvation induced an increase of CHX17 transcripts in wild-type plants; and K 1 starvation caused a 20% decrease in K 1 content of chx17 mutant roots (Cellier et al, 2004). To offset alkalization of the cytosol in yeast grown at pH 7.5, we suggest that antiporters, like CHX20, neutralize cytosolic pH by mediating K 1 exchange for H 1 release from acidified compartments.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed 18 CHXs are preferentially expressed in pollen and six AtCHXs are highly expressed in roots and/or shoots (Cellier et al, 2004;Sze et al, 2004;Hall et al, 2006). However, a discrepancy in the spatial expression of CHX23 mainly in either pollen (Sze et al, 2004) or sporophytic tissues (Song et al, 2004) raises concerns about unconfirmed results.…”
Section: Discussionmentioning
confidence: 99%
“…However, since the aha2 mutant plants show growth differences such as reduced sensitivity to toxic cations and an enhanced sensitivity to environmental stresses that challenge the plasma membrane PMF, the identities of these 27 genes could provide useful information on the plant's responses to genetically induced changes in plasma membrane energetics. Among the up-regulated mRNAs observed in aha2 mutants are, notably, a potassium transporter (AtHAK5) and a proton/potassium antiporter (K + /H + exchanger 17) known to be induced under potassium starvation (Cellier et al, 2004;Gierth et al, 2005;Maresova and Sychrova, 2006). Changes in the expression of potassium transporter genes may provide avenues by which the plant cells compensate for reductions in turgor caused by a reduced membrane potential in the mutant.…”
Section: Transcriptome Analysis Of Aha1-6 and Aha2-4 Mutantsmentioning
confidence: 99%
“…• C with a light intensity maintained above 300 µE · s −1 · m −2 and a day/night regime of 16 h/8 h. For determining the expression pattern of ACO genes, wild-type (Col ecotype) plants were grown under hydroponic conditions for 5 weeks as described in [23]. The other studies were performed on 10-day-old plantlets grown in liquid medium under sterile conditions [13].…”
Section: Plant Culturementioning
confidence: 99%